IMPLEMENTASI SMART SCHOOL DALAM MANAJEMEN KESISWAAN PENDIDIKAN ANAK USIA DINI UNTUK MENINGKATKAN EFEKTIVITAS LAYANAN - Aprilia Doni Setiani; Arfina Hikmawati; Fetty Ernawati (Jurnal Pendidikan Nusantara, 2026)
This study aims to analyze the implementation of Smart School in student management in early childhood education (ECE) and its impact on the effectiveness of educational services. The study employs a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving the principal, teachers, and parents as research subjects. The findings indicate that the implementation of Smart School has been carried out through the digitalization of student administration, the use of automated attendance systems, digital student cards, and integrated monitoring dashboards. In addition, communication between schools and parents is conducted through digital media, enabling faster and more continuous information delivery. This implementation contributes to improving the effectiveness of educational services, as reflected in administrative efficiency, ease of access to information, increased parental satisfaction, and more structured monitoring of children's development. However, several challenges remain, including limited internet infrastructure and the adaptation of teachers to digital technology. Overall, the implementation of Smart School in ECE student management contributes positively to improving technology-based educational service quality.